HUBUNGAN ANTARA KESADARAN PROFESI, VARIASI ASAL SEKOLAH DAN PERSEPSI TERHADAP PERKULIAHAN DENGAN PEROLEHAN HASIL BELAJAR PADA MAHASISWA PENYETARAAN S-l PGSM JURUSAN P. MIPA - SUMANTO SUMANTO; SRI DWIASTUTI (Bioedukasi: Jurnal Pendidikan Biologi, 2004)
The objective of this research was to know the significant correlation between profession awareness, previous school belonging and perception toward teaching with acquisition of study yield on the student of graduate-degree equalizing program of PGSM on the department of Mathematics and Natural Science Education.Descriptive analysis characterized by expost facto was used. Data was collected upon 40 student of PGSM. Anareg and Analysis of Variant with dummy variables were used with the degree of significant of p>0.05.The result showed that there is a positive correlation, which is not significant between profession awareness, previous school belonging and the perception toward teaching with acquisition of study yield on the student (R=406; p=0,086, thus p>0,05)